Propagação da aceroleira (Malpighia glabra L.) através de métodos de enxertia em função da posição do propágulo na planta matriz - Vieira, Clemens de Paula Gomes (1996)
The experiment was conducted in the nursery of plants of the Mossoró Agro-industrial S/A (MAISA) in Mossoró, Rio Grande do Norte, Brazil from april to october 1995, with principal objective to test grafting methods to propagation of the West Indian cherry (Malpighia glabra L.), in duty of the position of the propagule in the mother plant, using rootstocks with age of five months after planting date and 5,0 to 7,0 mm in diameter on the operatory zone. A randomized block design with two replications and twelve treatments was used in fatorial scheme 4 x 3, namely, four puffing methods (normal T and shield buddings, whip and side graftings) and three positions of the propagule in the mother plant (bottom, middle and top). The experimental plot was composed for twenty plants. The grafting sucess was evaluated at the 20, 30, 40, 50 and 60 days after the grafting procedure. The data obtained at the 60 days showed that the larger percentage of take, number of buds and leafs were attained by syde grafting (higher than 88%; 4,31 and 15,45) and whip grafting (higher than 64%; 2,67 and 10,60), independent of the position of the propagule. The whip and syde grafting methods evaluated can be recommended as a comercial method for asexual propagation of West Indian cherry tree.